2009
DOI: 10.1186/1939-4551-2-2-13
|View full text |Cite
|
Sign up to set email alerts
|

''United Airways Disease'' and Phenotypic Peculiarities of Respiratory Allergy in Immigrants

Abstract: Allergy is the result of a complex interaction between genetic background and environmental factors, including exposure to allergens and lifestyle. Migration is a process that involves many radical changes in the environment, including diet, pollutants, allergens, different housing conditions, and patterns of infections. Thus, studies in immigrants may provide important information about the role of environmental factors in the development of allergic respiratory diseases. Several studies addressed this aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Perhaps, a longitudinal study may reveal further information on the pathogenic role of local environmental conditions in sensitized individuals. Further studies consistently found that immigrants tended to develop allergies at different rates with symptoms often appearing 3 to 5 years after settlement into new environment [13]. This was observed in our study as more migrants in our study reported developing allergy after migration.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Perhaps, a longitudinal study may reveal further information on the pathogenic role of local environmental conditions in sensitized individuals. Further studies consistently found that immigrants tended to develop allergies at different rates with symptoms often appearing 3 to 5 years after settlement into new environment [13]. This was observed in our study as more migrants in our study reported developing allergy after migration.…”
Section: Discussionsupporting
confidence: 80%
“…Numerous studies have concluded that any mutations or changes to genetic background would take many years and would affect the next generation whereas environmental conditions such as pollution, variability in microbiota and quite possibly genetically modified foods would account for the increasing development of allergic reactions [13,14]. In our study, alcohol consumption was the most reported factor among immigrant and nonimmigrant population, while food allergies, decrease sleep and lactose intolerance were also reported.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations